Mathematical problem solving proficiency of students with musical and kinesthetic intelligence - Ismaimuza, Dasa; Pathuddin, Pathuddin; Adawiyah, Rabiyatul (Jurnal Riset Pendidikan Matematika, 2023)
The purpose of this study was to obtain a description of the results of the analysis of mathematical problem solving for students with musical intelligence and kinesthetic intelligence. This type of research is qualitative research. The research subjects were one student with musical intelligence and one student with kinesthetic intelligence. The results of this study indicate: Students with musical intelligence have low problem-solving abilities. It can be seen from the students' ability to solve the given mathematical problems, that is, students are less thorough in obtaining information about what is known and asked, students are not able to express a plan to explain the problem solving plan they want to do. students do not write down the complete solution, students do the calculation again only in the final step. Meanwhile, students who have kinesthetic intelligence have good problem-solving skills. It can be seen from the students' ability to solve the given mathematical problems, namely students are able to express what is known and asked in the questions using their own language. students cannot express the steps to be taken in solving the problem, students write down in full what is known and asked in full, students re-examine the results of their work by looking at and recalculating the answers that have been obtained.